Answered

Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

prove that tan-1x + cot-1(x+1) = tan-1( 1 + x + X^2)

Sagot :

lhs=tan-1x+cot-1x=pi/2
=tan-1x+pi/2-tan-1(x+1)
now tan-1x-tan-1y=tan-1{(x-y)/[1-xy]}
so
=tan-1{(x-x-1)/(1+x+x^2)+pi/2
=tan-1{-1/(1+x+x^2)}+pi/2
tan is odd func.
so tan-1(-x)=-tan-1x and tan-1(1/x)=cot-1x
so
-cot-1(1+x+x^2)+pi/2
=tan-1(1+x+x^2)
so
lhs=rhs
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.